Inactivating mutations of the histone methyltransferase gene EZH2 in myeloid disorders. - Ernst, T; Chase, A; Score, J; Hidalgo-Curtis, C; Bryant, C; Jones, A; Waghorn, K; Zoi, K; Ross, F; Reiter, A; Hochhaus, A; Drexler, H; et al. (2010)
Abnormalities of chromosome 7q are common in myeloid malignancies, but no specific target genes have yet been identified. Here, we describe the finding of homozygous EZH2 mutations in 9 of 12 individuals with 7q acquired uniparental disomy. Screening of a total of 614 individuals with myeloid disorders revealed 49 monoallelic or biallelic EZH2 mutations in 42 individuals; the mutations were found most commonly in those with myelodysplastic/myeloproliferative neoplasms (27 out of 219 individuals, or 12%) and in those with myelofibrosis (4 out of 30 individuals, or 13%). EZH2 encodes the catalytic subunit of the polycomb repressive complex 2 (PRC2), a highly conserved histone H3 lysine 27 (H3K27) methyltransferase that influences stem cell renewal by epigenetic repression of genes involved in cell fate decisions. EZH2 has oncogenic activity, and its overexpression has previously been causally linked to differentiation blocks in epithelial tumors. Notably, the mutations we identified resulted in premature chain termination or direct abrogation of histone methyltransferase activity, suggesting that EZH2 acts as a tumor suppressor for myeloid malignancies.